PERPEKSTIF CUSTONER DALAM E-COMMERCE: STUDI KUALITATIF TENTANG PENGARUH DISKON DAN GRATIS ONGKIR TERHADAP MINAT BELI - R. Taufiq Nur Muftiyanto; Singgih Purnomo; Faulinda Ely Nastiti (JURNAL ILMIAH EDUNOMIKA, 2024)
E-commerce has become an integral part of consumer life, with the rapid growth of this industry. Customer perceptions of purchasing drivers are crucial in understanding consumer behavior within the E-commerce ecosystem. This research aims to explore customer perceptions regarding the influence of two main factors, namely discounts and free shipping, on purchase intent in the context of E-commerce. The research methodology employs a qualitative approach through literature review to elaborate on relevant previous studies concerning customer perceptions in E-commerce, particularly in the context of discounts and free shipping. The results of the literature review reveal various perspectives and findings that can provide in-depth insights into the impact of these two factors on consumer purchase intent. The research findings highlight that discounts and free shipping play a crucial role in shaping customer perceptions, significantly influencing their purchase intent. A brief discussion presents the key findings from the literature review, illustrating the contributions of each factor to purchase decisions. The conclusion of this study provides a holistic overview of the importance of discounts and free shipping in stimulating customer purchase intent in E-commerce. Practical implications and suggestions for further research are also discussed. Keywords : E-commerce, Customer Perception, Purchase Intent.